Investigation of the train schedule and headway for mass rapid transit - Nur Adibah, Abdul Wahab (2022)
On 17 July 2017, 31 stations of Mass Rapid Transit Kajang Line (MRT KGL) were fully operated. In just two years, the ridership of the KGL is about to exceed the ridership of the Ampang LRT Line which has been operated for 23 years. With the increase of the ridership, it may cause congestion in the platform and the uncertainty of train schedule and headway. Hence, it is important to design an optimal train timetable including train dwell time to avoid the service disruption caused by congestion. The KGL train model is simulated using the ETAP software, The optimized train schedule from the KGL is used as a parameter for the simulation. The performance of the train model is evaluated. The results shows that more trains quantity and short headway can minimize the passenger congestion at the platform because no passenger needs to wait for a long time for the train arrival, especially at the end-to-end stations.